2021
DOI: 10.1039/d1ee01530c
|View full text |Cite
|
Sign up to set email alerts
|

Battery cost forecasting: a review of methods and results with an outlook to 2050

Abstract: This review analyzes 53 publications that forecast battery cost and provides transparency on methodological and technological details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(147 citation statements)
references
References 153 publications
0
120
0
1
Order By: Relevance
“…While production costs are expected to decrease in the medium to long term due to economies of scale, learning curves and technical developments, this should be accompanied by the establishment of a circular production chain. [280] In this context, battery recycling is in constant competition with suppliers of virgin battery materials, both in terms of prices and material performance. [281,282] Several publications have indicated that better separation of material streams at the beginning of recycling can lead to higher product purity and recycling efficiency, contributing to a more competitive battery recycling industry.…”
Section: Design For Recyclingmentioning
confidence: 99%
“…While production costs are expected to decrease in the medium to long term due to economies of scale, learning curves and technical developments, this should be accompanied by the establishment of a circular production chain. [280] In this context, battery recycling is in constant competition with suppliers of virgin battery materials, both in terms of prices and material performance. [281,282] Several publications have indicated that better separation of material streams at the beginning of recycling can lead to higher product purity and recycling efficiency, contributing to a more competitive battery recycling industry.…”
Section: Design For Recyclingmentioning
confidence: 99%
“…The cost of lithium-ion batteries (LIB), the state-of-the-art technology in electric vehicles 4,5 and economically promising in stationary energy storage applications 6 , is considered too high to render battery-powered products fully competitive with their conventional counterparts 7 , even though it has decreased more than fivefold during the past decade 8 . On the one hand, this trend is expected to further continue in the future, as shown by a recent review of battery cost forecasting studies that use the methods of technological learning, literature-based projection, bottom-up modeling, and expert elicitation 9 . Major drivers of these expectations are technological advances in both, battery technology and production process 10 , and economies of scale by a global expansion of LIB production 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…9 On the one hand, this trend is expected to further continue in the future, as shown by a recent review of battery cost forecasting studies that use the methods of technological learning, literature-based projection, bottom-up modeling, and expert elicitation. 10 Major drivers of these expectations are technological advances in both, battery technology and its production process, 11 and economies of scale by a global expansion of LIB production. 12,13 On the other hand, industry analysts are increasingly concerned about rising prices for critical raw materials 14,15 as demand expectations are growing significantly and currently committed investments for future mining activities are considered insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several barriers and challenges for a 100% energy transition to find alternative technologies capable of mitigating the CO 2 problem through zero emissions or indiscriminate use of CO 2 in the air such as fuel-like photosynthesis [141]. In addition, batteries still represent the biggest obstacles due to their cost and short lifespan, as most countries are now turning to use electric vehicle charger stations (EVCSs) to make the environment clean [8,[142][143][144][145][146].…”
Section: Role Of Energy Storage Systems In Egyptmentioning
confidence: 99%